Increase in Thiol Oxidative Stress via Glutathione Reductase Inhibition as a Novel Approach to Enhance Cancer Sensitivity to X-Ray Irradiation - Zhao, Yong (2009)
Depletion of reduced form glutathione (GSH) has been extensively studied for its effect on sensitizing cancer to radiation. However, little is known about the effect of thiol oxidative stress created through an increase in glutathione disulfide (GSSG) on cancer sensitivity to radiation. In this study, an increase in GSSG was effectively created by 2-acetylamino-3-[4-(2-acetylamino-2-carboxyethylsulfanylthiocarbonylamino)phenylthiocarbamoylsulfanyl]propionic acid (2-AAPA), an irreversible glutathione reductase (GR) inhibitor. Our results demonstrate that the GSSG increase significantly enhanced cancer sensitivity to X-ray irradiation in four human cancer cell lines (A431, MCF7, NCI-H226 and OVCAR-3). When cells were pretreated with 2-AAPA followed by X-ray irradiation, the IC(50) values of X-ray for A431, MCF7, NCI-H226 and OVCAR-3 cells were reduced from 24.2±2.8, 42.5±3.0, 43.0±3.6 and 27.8±3.5 Gy to 6.75 ±0.9, 8.1±1.1, 6.75±1.0, and 12.1±1.7 Gy respectively. The synergistic effects observed from the combination of X-ray plus 2-AAPA were comparable to that from the combination of X-ray plus buthionine sulfoximine (BSO), a reference compound known to increase cancer sensitivity to radiation. The synergistic effect was correlated with an increase in cell thiol oxidative stress which was reflected by a 5–6 fold increase in GSSG and 25% increase in total disulfides. No change in GSH and total thiols was observed as a result of GR inhibition.